Eine Reichsteilung bei Josephus Flavius Beobachtungen zu seiner Auffassung von Daniel 5 - Höffken, Peter 1940-2007 (2005)
This article seeks to show that the idea in Josephus, Ant 10:232-248, that the Babylonian empire was divided between Darius the Mede and Cyrus the Persian has developed from different texts in the Old Testament that speak about the fall of Babylon through Medes or the Persian Cyrus. The article discusses some materials in Josephus that show that the author is doing similar things elsewhere in his work.
Keywords: Josephus, Flavius -- 37-100; Bibel